Sistem Informasi Geografis Rekomendasi Partisipasi Publik Ruang Terbuka Hijau Berbasis Android Mobile (Studi Kasus : Kota Malang) - Roudhotul Ridho Akbar; Fatwa Ramdani; Aryo Pinandito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Urban green space (RTH:Ruang Terbuka Hijau in Bahasa) is the spaces within the city or the wider region in the form of area/region as well as in the form of the area extend path gives the benefits of ecological, social, cultural, economic and aesthetic to urban environments. According to the Board Indonesian Forum for the Environment (Walhi) East Java by 2016, RTH in the Malang City, reaching only 2% of the territory of the Malang City. At this time many residents who have been demanding greater participation in establish public policy decisions that government affect. Malang is also the difficulty in finding RTH in the Malang City, only 3.6% of his only RTH is known in the Malang City. Geographic information system recommendation of public participation urban green space is one of breakthrough for community to participate in giving recommendation of RTH in Malang City. By utilizing LBS (Location Based Service) technology and Geotagging on the android device allows the community to provide recommendations RTH that desired of the community. This information system also helps the community in facilitating to find RTH in Malang city. So the government more facilitated in determining the development of RTH in Malang city.